Optimalisasi Kompetensi Komunikasi Digital Guru SMP melalui Workshop Artificial Intelligence - Ibad, M. Nashoihul (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to optimize junior high school teachers’ digital communication competence through an Artificial Intelligence workshop at SMPN 2 Pungging, Mojokerto. The program was motivated by teachers’ limited ability to integrate AI and computational thinking into cross-curricular learning, as well as the underutilization of AI for academic administration and instructional material development. The method employed was a participatory workshop consisting of interactive lectures, demonstrations, independent practice, discussions, mentoring, and peer teaching. The materials covered policies on coding and artificial intelligence in education, prompt engineering, lesson module development, AI-based assessment, AI ethics, and classroom implementation. The results showed improvements in AI literacy, digital skills, teachers’ ability to develop instructional materials, and their self-confidence. Approximately 90% of participants were able to use AI directly and produce AI-based learning products. This activity strengthened more interactive, contextual, and responsive classroom communication.